Making the connections: Using health care research in nursing clinical teaching practice - Lada, Nancy Schoales (University of Ottawa (Canada), 2006)
Studies show nurses experience many barriers to research use in practice. Nursing education needs to prepare nurses to evaluate and apply research as a basis for practice. Clinical teachers have the opportunity to close the gap between research and practice by preparing students to use research in their practice. However, little is known about how clinical teachers use health care research in nursing clinical teaching practice. The purpose of this qualitative research study is to explore the use of health care research in nursing clinical teaching practice. Study objectives are: (a) to explore the use of health care research by clinical teachers (current practices); (b) to examine clinical teachers' concerns about using health care research in their practice; (c) to explore factors that impede or facilitate clinical teachers' use of health care research in their teaching; and (d) to explore strategies used by clinical teachers to promote use of heath care research by students. A grounded theory approach was used. A convenience sample of 15 clinical teachers in a baccalaureate nursing collaborative program were interviewed using a semi-structured questionnaire. Analysis of the data led to the identification of the main theme making the connections. Also identified were the sub categories of valuing the connections, conditions affecting the connections, connections strategies, students seeing the connections and strengthening the connections. The findings were presented to 9 of the original 15 participants and feedback indicated they agreed with the results of analysis and the model developed. Implications for nurses teaching clinical practice, nurses in full-time faculty or administrative roles and research are discussed.
Keywords: Health Sciences, Nursing.